Triphenylphosphine Oxide-Catalyzed Selective α,β-Reduction of Conjugated Polyunsaturated Ketones - Xia, Xuanshu; Lao, Zhiqi; Toy, Patrick H. (Synlett, 2019)
The scope of the triphenylphosphine oxide-catalyzed reduction of conjugated polyunsaturated ketones using trichlorosilane as the reducing reagent has been examined. In all cases studied, the α,β-C=C double bond was selectively reduced to a C–C single bond while all other reducible functional groups remained unchanged. This reaction was applied to a large variety of conjugated dienones, a trienone, and a tetraenone. Additionally, a tandem one-pot Wittig/conjugate-reduction reaction sequence was developed to produce γ,δ-unsaturated ketones directly from simple building blocks. In these reactions the byproduct of the Wittig reaction served as the catalyst for the reduction reaction. This strategy was then used in the synthesis of naturally occurring moth pheromones to demonstrate its utility in the context of natural-product synthesis.
Keywords: triphenylphosphine oxide; trichlorosilane; reduction; Lewis base; organocatalysis; pheromones